Proleptic leadership on the commons : ushering in a new global order - Thompson, Randal Joy (Emerald Publishing Limited, 2020)
Capitalism is in crisis and, according to some, on the verge of collapse. Will this dying system give way to a commons-centric society as many scholars and activists predict? Will leadership become an antedated function, no longer needed in the self-organized, collaborative commons? These questions inspired the author of Proleptic Leadership on the Commons: Ushering in a New Global Order to explore the history of the commons movement, the recent systems frameworks that carve out a transformational commons path forward, and the leadership theories that honor the chaos and complexity of our times and encourage emergent change toward a more egalitarian society based on care, obligation, and collaboration. Viewing the commons as a vehicle for a new world order, Randal Joy Thompson proposes 'proleptic leadership', which envisions how leaders will continue to be essential in a commons-centric world as the custodians of responsible agency and conscious choice. Mapping out how leaders can achieve higher levels of consciousness and traverse liminal space in order to be ethical and caring agents of change, this book challenges us to reflect on our commitment to creating a more nurturing future, and evaluate how our own qualities might help manifest, or perhaps hinder, that future.
Includes index.
Keywords: Commons -- Economic aspects.; Commons -- Political aspects.; Leadership -- Philosophy.; Business & Economics -- Economics -- Comparative.; Economic theory & philosophy.; elektronické knihy; electronic books